2021
DOI: 10.1088/1742-6596/1764/1/012201
|View full text |Cite
|
Sign up to set email alerts
|

Minimize waste on production process using lean concept

Abstract: This research aims to analyze and minimize the waste that occurs in the production process by using a lean production approach. One of the factors that can influence ineffective and inefficient in the production process is waste in the production process. An effective and efficient pr oduction process will support the company to increase productivity. The problems that occur in company X are companies that still often experience delays in meeting consumer demand, and there are still defect products. These prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Use of VSM and Kaizen method helped to minimize the machine setup time and to remove other non value-added activities. Dewi et al (2021) studied a production company that often delayed to fulfill the customer demand, also a produced defective products. They observed that non value added activities consumed 59.8% time.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Use of VSM and Kaizen method helped to minimize the machine setup time and to remove other non value-added activities. Dewi et al (2021) studied a production company that often delayed to fulfill the customer demand, also a produced defective products. They observed that non value added activities consumed 59.8% time.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Permasalahan ini sejenis dengan permasalahan proses produksi yang dihadapi oleh produsen mebel (Fitri et al, 2022) Penerapan Lean Manufacturing menggunakan metode Value Stream Mapping (VSM) dan Failure Mode and Effect Analysis (FMEA) didapatkan hasil bahwa bobot waste defect 4,2; uncessary inventory 3,9; waiting 3,3; excessive transportation 3,1; uncessary motion 3,0 sehingga diperlukan usulan perbaikan untuk meningkatkan efisiensi pada proses produksi (Rido et al, 2020), juga ditemukan pemborosan yang terjadi di lantai produksi. Hasil sejenis juga ditemukan pada penelitian di produsen sarung tangan dan hanger (Octaviany et al, 2017;Ristyowati et al, 2017) Penerapan Lean Manufacturing pada kegiatan yang tidak bernilai tambah yang jumlahnya sangat signifikan perlu dilakukannya perbaikan pada aliran proses produksi agar menghasilkan peningkatan produktivitas (Dewi et al, 2021;Siregar et al, 2018;Wicaksono et al, 2019) dan ditemukannya pemborosan di lantai produksi (Salwin et al, 2021;Zakaria & Rochmoeljati, 2020) sehingga disarankan untuk dilakukan perbaikan.…”
Section: A Pendahuluanunclassified
“…According to Dewi et al [16], waste is caused by operational activities. The author identified seven types of operational waste: overproduction, waiting, movement transportation, unnecessary processes, inventory, and defects.…”
Section: B Waste Minimization In Operations Schedulingmentioning
confidence: 99%